2018
DOI: 10.1161/circheartfailure.117.004628
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Readmissions After Left Ventricular Assist Device Implantation in the United States

Abstract: Early readmissions are frequent after LVAD implantation even in contemporary times. Preimplant identification of high-risk patients, and a protocol-driven follow-up using a multidisciplinary approach will be needed to reduce readmissions and improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…All analyses were performed using SPSS version 23.0 (IBM Corp., Armonk, NY) on unweighted NRD data using similar statistical methods as previously published. [5][6][7] Differences between categorical variables were tested using the χ 2 test and continuous variables by using the Student t test. The annual cost impact of index and 1-month readmissions was analyzed using weighted samples to estimate national averages.…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were performed using SPSS version 23.0 (IBM Corp., Armonk, NY) on unweighted NRD data using similar statistical methods as previously published. [5][6][7] Differences between categorical variables were tested using the χ 2 test and continuous variables by using the Student t test. The annual cost impact of index and 1-month readmissions was analyzed using weighted samples to estimate national averages.…”
Section: Discussionmentioning
confidence: 99%
“…In several series, major infection was shown as one of the most common causes of readmissions. [5,14,19,20] In our study group, it was also the frequent and repetitive cause for hospitalization. Subgroup analyses revealed that 56% of all readmissions due to infection were device-related.…”
Section: Discussionmentioning
confidence: 59%
“…Our study has several limitations due to the administrative nature of the national databases and their reliance on accuracy of coding as noted in previously published studies evaluating myocardial infarction patients . The nature of the codes available may not have been completely representative of LV thrombus and thus the incidence of thrombus in our study was far lower than previously reported, and can be attributed to the reliance on coding.…”
Section: Discussionmentioning
confidence: 74%